Lymphopenia at diagnosis predicts survival of patients with immunodeficiency-associated lymphoproliferative disorders - Watanabe, Mizuki; Kanda, Junya; Hishizawa, Masakatsu; Nishikori, Momoko; Kondo, Tadakazu; Yamashita, Kouhei; Takaori-Kondo, Akifumi (Annals of hematology, 2020)
The number of patients who are administered immunosuppressive agents has been increasing. Accordingly, more patients face higher risks for developing immunodeficiency-associated lymphoproliferative disorders (LPD). Although immunodeficiency-associated LPD are distinct from other lymphoid neoplasms in terms of their immunocompromised backgrounds, little is known about the impact of lymphopenia at diagnosis on survival in patients with these LPD. Seventy-one immunodeficiency-associated LPD in Kyoto University Hospital (post-transplant LPD (PTLD), n = 26; other iatrogenic immunodeficiency-associated LPD, n = 45) were reviewed and analyzed. The median age at diagnosis was 63 years (range, 3–83). Diffuse large B cell lymphoma was the most common subtype ( n = 33), followed by Hodgkin lymphoma ( n = 12), B cell monomorphic LPD not specified ( n = 11), and polymorphic LPD or early-phase diseases ( n = 15). The median follow-up period for survivors was 2.5 years and overall survival (OS) and progression-free survival (PFS) at 2.5 years were 75% and 67%, respectively. Multivariate analysis showed that lymphopenia (≤ 800/μL) at diagnosis predicted inferior OS (HR, 3.72; P = 0.043) and PFS (HR, 3.82; P = 0.012). Serum albumin values also strongly affected OS (> 3.18 g/dL vs. ≤ 3.18 g/dL; HR, 0.21; P = 0.010) and PFS (HR, 0.26; P = 0.013). Lymphopenia at diagnosis is suggested to predict inferior OS and PFS in patients with immunodeficiency-associated LPDs. Immunocompromised status might affect disease progression in these distinct lymphoid neoplasms growing under immunocompromised backgrounds.